Perbandingan Performa Framework Laravel dengan ExpressJS Pada Pengembangan Aplikasi Homestay Kosasih - Hartono, Zhidan Fahrus Yas; Umam, Khoirul; Hakim, Lukman; Prasetyo, Junaedi Adi; Febrita, Ruth Ema (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
The rapid development of information technology, including web application development, demands the selection of an optimal framework to achieve the desired performance. Homestay Kosasih had used Laravel as its development framework, but faced performance challenges such as increased response times and higher resource usage. This research aims to compare the performance of Laravel (based on PHP) and ExpressJS (based on JavaScript) in the context of Kosasih Homestay application development. The research method uses a quantitative approach with direct performance testing on both frameworks, measuring loading time, responsiveness and efficiency of resource use. The results show that ExpressJS has faster response times and more efficient resource usage than Laravel. However, Laravel excels in ease of development and complete built-in features. The conclusion of this research is that ExpressJS is more recommended for applications that require high performance and efficiency, while Laravel is more suitable for development that requires complete built-in features. These findings provide insight for the development team in choosing the most appropriate framework to improve the performance and responsiveness of the Homestay Kosasih application.